Study on the Effect of Biourine and Mycorrhizal Arbuscular Fungi towards Result and Value of Forage Nutrition Hymenachne amplexicaulis (Rudge) Nees) on the of Ex-Coal Mine Land: An Advanced Study - Hardi Syafria; Novirman Jamarun (Research Aspects in Agriculture and Veterinary Science Vol. 2, 2021)
The purpose of this study is to find, obtain and prove that, the administration of biourine and the fungi of mycorrhiza arbuskula (FMA) is able to improve the fertility of ex-coal mine land, so that it gives an influence on the results and nutritional value of forage feed. This experiment used a completely randomized design with 4 treatments and 5 replications. The treatment consists of: 1) concentration of 0% biourine + FMA 20 g/pot, 2) concentration of 15% biourine + FMA 20 g/pot, 3) concentration of 30% biourine+ FMA 20 g/pot and 4) concentration of 45% biourine + FMA 20 g/pot. Variables observed were the results of dry matter, crude protein, dry matter digestibility, organic digestibility by In-Vitro and percentage of root infections by mycorrhizae. This results of the analysis of variance showed that the treatment had a very significant effect (P<0.01) on all observed variables. The treatment of 45% biourin + FMA 20 g/pot produced the highest value, followed by the treatment of 30% biourine + FMA 20 g/pot, 15% biourine + FMA 20 g/pot and the treatment of 0% biourine + FMA 20 g/pot. The conclusion of this study was that the treatment concentration of 45% biourine + FMA 20 g/pot was the best of all the observed variables.